Pengaruh Persentase dan Keberadaan Perempuan Hindu dalam Jajaran Pengurus pada Kinerja Bank Perkreditan Rakyat di Bali - Sudiana, I Wayan; Muliati, Ni Ketut; Suardika, Anak Agung Ketut Agus; Yuniasih, Ni Wayan (E-Jurnal Akuntansi; Vol 31 No 4 (2021)DO - 10.24843/EJA.2021.v31.i04.p12, 2021)
Research on the influence of women on company performance has shown inconsistent results. This study wanted to determine the effect of the percentage and presence of Hindu women in the board of directors on the performance of BPRs in Bali. Gender in this study is seen from two aspects, namely the percentage and the presence of female board members. The population in this study was all rural banks in Bali. The sample was determined by using purposive sampling technique and obtained 110 companies that met the criteria. Hypothesis testing is done using multiple regression analysis. The results showed that the percentage of Hindu female board members had no effect on company performance, while the presence of Hindu female board members had a positive effect on company performance. Keywords: Gender Diversity; Hindu Women; Firm Performance.